The Teutonic Knights in the Southern Hungarian Kingdom: Preparation for Battle - Oța, Silviu (Before the Battle, 2023)
Until now, the presence of Teutonic knights in the 15th century was analysed mainly based on historical sources. The publications to date focused on the causes of the Teutonic Order’s arrival, the results of their actions, the area they received for administration, and the fortifications they controlled. In this regard, we can mention the works of T. H. Trâpcea (1969), Alexandru Nemoianu (1975), Ioan Hațegan (1979), Eugen Glück (1992), Viorel Achim (2013 and 2014), and Costin Feneșan (2015).The information acquired from written records comes primarily from the documents found in the Teutonic Order’s archives. However, other sources also mention the Knights’ presence and activities in the Banate. These records were also used by Romanian historians to analyse the Knights’ relationship with the local population. The Teutonic Knights – namely a group of 13 Knights under the leadership of Klaus von Redwitz – arrived in Hungary in the autumn of 1429 at the request of King Sigismund of Luxembourg and withdrew from the Banate 1434 or 1435. Nineteen fortifications on the Danube and three located further north (Almăj, Ilidia/Socolari, Mehadia) were assigned to them. Two others (Carașova and Bârzava) were also in Wallachia but were not mentioned and their obligations. Archaeological excavations have been made In the last 50 years, archaeologists carried out excavation works in some fortifications previously administrated by the Teutons: at Drobeta-Turnu Severin), Tricule-Svinița, Saint Ladislau, and in auxiliary fortifications which primarily role was to supply goods and people (Carașova, Mehadia, Ilidia/Socolari).The preparations for battle with the Ottomans made by the 13 Teutonic knights and their retinues proved to be without great results. Furthermore, the amounts required by the Teutonic Knights to cover the most necessary expenses amounted to 346 140 florins per year, a sum too high for the economic capabilities of the Middle Danube region to be raised locally. The Ottoman campaigns of 1432 and 1433 led to the destruction of some fortresses and of their garrisons, including Severin and St. Ladislau. The tactics of the defenders to lock themselves in the fortresses proved to be inefficient when they had to fight with extremely mobile and numerous Ottoman armies.The Banat is currently the region of southwestern Romania and partly Serbia east of the Tisza River and Hungary, the portion between the Mureș River to the north and the Tisa. In the Middle Ages, with some interruptions, there was also Western Oltenia, Banatul de Severin, in the part of the current region. Its borders were fluctuating. It followed chronologically that of Lugoj-Caransebeș (created gradually between the years 1526–1536), in the east of the current Banat, integrated into the Principality of Transylvania. It partially overlapped the Banat of Severin. In the modern period, the entire region between the rivers Mureș, Tisa, the Danube and the Carpathian Mountains was known as Banat. In the following, I will use the generic name of Banat.